Problemy terminologiczne w glottodydaktyce – źródła, przykłady, konsekwencje - Aleksandrzak, Magdalena (Neofilolog, 2021)
The present paper discusses selected terminological problems typical of the field of foreign language teaching and learning. The discussion concentrates on several terms commonly used in various glottodidactic debates, namely: competence, communication, interaction, discourse, authenticity and individual differences. The article attempts to indicate the sources of inconsistencies in the terminology, offers several examples and interpretations of these terms in questions from the relevant literature, and determines potential consequences. The aim of the paper is also to indicate areas of glottodidactic research which may be particularly sensitive to such terminological confusion and to stress the necessity of identifying the theoretical perspective and defining the terms central to the particular research project or discussion.